Development of tourism indystry in Lviv - Marshalenko, Marianna (My University, 2018)
Issues of tourism industry development in Lviv are discussed.
Keywords: туризм; туристична індустрія; Львів; кафедра готельно-ресторанної справи; туристическая индустрия; Львов; tourism; tourism industry; Lviv